2016
DOI: 10.7554/elife.19092
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA produced by RNA polymerase V determines boundaries of heterochromatin

Abstract: RNA-mediated transcriptional gene silencing is a conserved process where small RNAs target transposons and other sequences for repression by establishing chromatin modifications. A central element of this process are long non-coding RNAs (lncRNA), which in Arabidopsis thaliana are produced by a specialized RNA polymerase known as Pol V. Here we show that non-coding transcription by Pol V is controlled by preexisting chromatin modifications located within the transcribed regions. Most Pol V transcripts are asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 64 publications
(185 reference statements)
8
86
0
2
Order By: Relevance
“…Methylation of the Tto internal CDS region is consistently lower than methylation at the LTRs ( Figure 4D), suggesting that the CDS does not cause element recognition and that the LTRs drive silencing. This correlates with published data demonstrating that the ends of endogenous long TEs are preferentially targeted by RdDM mechanisms (Zemach et al, 2013;Böhmdorfer et al, 2016).…”
Section: Full Tto Elements Transition To Maintenance Methylation Andsupporting
confidence: 80%
“…Methylation of the Tto internal CDS region is consistently lower than methylation at the LTRs ( Figure 4D), suggesting that the CDS does not cause element recognition and that the LTRs drive silencing. This correlates with published data demonstrating that the ends of endogenous long TEs are preferentially targeted by RdDM mechanisms (Zemach et al, 2013;Böhmdorfer et al, 2016).…”
Section: Full Tto Elements Transition To Maintenance Methylation Andsupporting
confidence: 80%
“…() revealed extensive symmetrical and asymmetrical DNA methylation in the BIR1 promoter, whereas methylation was drastically diminished in nrpe1 compared with wild‐type plants (Figs a, S3). Furthermore, published Pol V RIP‐seq data (Bohmdorfer et al ., ) revealed that Pol V‐associated RNA accumulated in the Col‐0 wild‐type, but not in nrpe1 mutants, confirming that RNA reads originated at the BIR1 promoter were associated with Pol V (Fig. a).…”
Section: Resultsmentioning
confidence: 57%
“…The circle graph represents the size distribution of BIR1 ‐derived siRNAs. The genome browser screenshot of CHH methylation and Pol V transcripts at the BIR1 promoter in wild‐type (Col‐0) and nrpe1 mutants using whole‐genome bisulfite sequencing (WGBS) and Pol V (NRPE1) RIP‐seq datasets is shown (Wierzbicki et al ., ; Bohmdorfer et al ., ) (lower diagram). (b) Accumulation of BIR1 transcripts in rosette leaves of wild‐type and RdDM mutants ( cmt3 , drm2 , ddc , nrpe1 and ago4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent detection of Pol V lncRNAs and the demonstration of their association with downstream components of the RdDM pathway, including AGO4, led to the proposal of an RNAbased mechanism for RITS guiding to target loci (Wierzbicki et al 2008(Wierzbicki et al , 2009. The generality of a Pol V-based targeting model was further supported by whole-genome studies that revealed a high degree of overlap between the sets of genomic regions bound and transcribed by Pol V and those harboring 24-nt siRNA-dependent DNA methylation (Wierzbicki et al 2012;Zhong et al 2012;Böhmdorfer et al 2016).…”
mentioning
confidence: 77%